The South Pole expedition of Roald Amundsen: how did he prepare for the expedition and what do his crewmembers' diaries tell us about it? / Geir O. Kløver. - Kløver, Geir Olav (Nimrod : the Journal of the Ernest Shackleton Autumn School, 2012)
Describes Amundsen's experience on de Gerlache's 1897-99 Belgica Antarctic expedition, scientific interests, lessons learned on his 1903-06 Gjøa Northwest Passage expedition, and experience on 1910-12 Fram Antarctic expedition. Gives details of crew members on Antarctic expedition with account of their diaries. Author is director of Fram Museum and editor of South Pole diaries of Amundsen and fourteen of his crew members.
Keywords: Antarktis; Belgica ekspedisjon; Sydpolsekspedisjonen; dagbøker; polarhistorie

Cecilie Skog. Liv Arnesen. Monica Kristensen - Sandberg, Sigri (Polarheltinner : Cecilie Skog, Liv Arnesen, Monica Kristensen, Christiane Ritter, Wanny Woldstad, Ellen Dorthea Nøis, Hanna Resvoll-Holmsen, 2012)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjoner; biografier; friluftsliv; kvinner; polarekspedisjoner; polarhistorie

Of reindeer, ponies and automobiles : Roald Amundsen and the Norwegian bid for the South Pole - Turney, Chris (1912 : the year the world discovered Antarctica, 2012)
Keywords: Antarktis; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie